2017
DOI: 10.1088/1748-9326/aa86dd
|View full text |Cite
|
Sign up to set email alerts
|

Indoor human exposure to size-fractionated aerosols during the 2015 Southeast Asian smoke haze and assessment of exposure mitigation strategies

Abstract: The 2015 smoke haze episode was one of the most severe and prolonged transboundary air pollution events ever seen in Southeast Asia (SEA), affecting the air quality of several countries within the region including Indonesia, Malaysia and Singapore. The 24 h mean outdoor PM 2.5 (particulate matter (PM) with aerodynamic diameter ≤ 2.5 m) concentrations ranged from 72-157 g m −3 in Singapore during this episode, exceeding the WHO 24 h mean PM 2.5 guidelines (25 g m −3 ) several times over. The smoke haze episode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…The prevalence of SBS was higher among occupants who lived in houses with no fan. Other studies also reported similar findings [ 40 , 41 ]. This is because fan-assisted ventilation improves the quality of the indoor air [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of SBS was higher among occupants who lived in houses with no fan. Other studies also reported similar findings [ 40 , 41 ]. This is because fan-assisted ventilation improves the quality of the indoor air [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 82%
“…The climate is facing two monsoonal winds, which initiate from the northeast among October and February, and from the southwest between May and September (Cheong et al 2013). Some countries of Southeast Asia has faced a severe event of haze in 2015 (Sharma and Balasubramanian 2019). Figure 1 shows the study area Kuala Lumpur.…”
Section: Study Areamentioning
confidence: 99%
“…Calculating ELCR using cancer potency values provided by OEHHA and USEPA, along with the CDI value, which incorporates several exposure factors such as body weight and breathing rate, is a more robust method of cancer risk determination. Sharma and Balasubramanian (2017) in their paper examining wildfire smoke haze-related …”
Section: Cancer and Non-cancer Risk Calculationsmentioning
confidence: 99%